EL MESTIZAJE LITERARIO PERUANO: DEL INCA GARCILASO A VARGAS LLOSA* - Martos Carrera, Marco (2005)
Two great cultures, the European and the Andean embrace to become onein Peru, a fusion made evident in its literature. Writers such as Garcilaso theInca and Guaman Poma strive to express themselves in a language nottheirs. Arguedas chooses the variant (Quechua or Spanish) that best suitshis interests; Vallejo recurs to a broken syntax to reveal his caotic innerfears. In Mario Vargas Llosa's writing the European language wins easily,el ose to the decanted Spanish of Garcilaso and the tricky style of GuamanPoma. In all these writers, one language lives within the other, a cultureinside another culture.